Reasons for growing vertical sex segregation in adulthood - Häfeli, Kurt; Hättich, Achim; Schellenberg, Claudia; Schmaeh, Nicolas (Swiss Journal of Educational Research, 2018)
Which are possible reasons for persistent gender differences in career success (e.g. in occupational status)? Based on a random sample of 485 persons representative of the German-speaking region of Switzerland the professional development between the ages of 15 up until 49 can be traced. There were major differences between men and women in terms of career steps: often women began their careers at a higher level than men but later showed significantly less vertical mobility. This has a lot to do with traditional division of roles; interruptions of one’s career for family reasons also have a negative impact on one’s occupational status. The initial and continuing training activities of men in this phase, however, seem to have a positive effect. It is interesting to note that factors from one’s youth also have a long-lasting impact (e.g. intelligence or personality characteristics).